Village autonomy in the development of Pagarbatu tourism village - Boemiya Helmy; Wahyuliana Ida; Firdiyansyah Erik; Yasa Muhammad (BIO Web of Conferences)
Tourism villages are tourism products that are developed based on the potential of the village. The concept of the tourist village is in line with the concept of village autonomy whose implementation is based on customs, village potential, and the origin of the village community. Pagarbatu Village is one of the tourist villages that has potential such as Tawaf Lengleng Hill as a source of sulfur, Ulagul/Tong-tong art, Saroneng, Muangsangkal dance, seaweed cultivation, and community awareness in tourism development. This is the reason for the research in Pagarbatu Village, Saronggi District, Sumenep Regency. This study aims to analyze the importance of village autonomy in the development of Pagarbatu tourism village and to find out the development of Tawaf Lengleng Hill tourism as an attraction owned by Pagarbatu village, Saronggi District, Sumenep Regency. The research method used is empirical research with a qualitative approach. The results of the study show that Pagarbatu Tourism Village shows several weaknesses in meeting the parameters of village autonomy success, especially in economic independence, resource management, community participation, service quality, government capacity, and sustainability. On the Tawaf Lengleng Hill there is inadequate infrastructure and limited marketing strategies have hindered the potential for further development, so it is necessary to improve the road to the site, improve supporting facilities such as parking and toilets, as well as add safety systems for visitors, work with travel agents and tour operators to expand market reach, encourage more community involvement in management, promotion, and development of tourism products, developing sustainability plans for sulfur resource management and environmental conservation involving local communities.